Data Management for Social Scientists: From Files to Databases - Kar, Sanjoy (Journal of Data Science, Informetrics, and Citation Studies)
The “data revolution” has presented social science researchers with a plethora of exciting new avenues of inquiry. It is becoming increasingly possible to record traces of social and political interactions digitally, which results in enormous volumes of fresh data that are made available for research. The concept of big data has gained significant attention in scientific disciplines (Floridi, 2012). However, despite the potential for big data and novel data sources to revolutionize research in the social sciences, their practical value and relevance to certain subject areas are not fully reached due to a lack of awareness (Kitchin, 2014; O’Brien, Sampson, & Winship, 2015). While some domains of the social sciences have a more unified approach to research using well-defined scientific methods and hypothesis testing to verify or falsify theories, other subjects, such as sociology (Leavy, 2014) and human geography, have a broader range of philosophical approaches (Kitchin, 2013; DeLyser, & Sui, 2014).